Komunikasi Visual pada Acuk Kuda Renggong - Supriatna - (LP2M ISBI Bandung, 2014)
ABSTRACT Kuda Renggong is a distinctive traditional performing art in Sumedang regency, which uses the horse as the main medium of expression. The most prominent element of Kuda Renggong is its visual element. That is form of a horse costume. This research method uses a ethnosemiotic approach, with re- sult of an interpretative meanings. Horse costumes are not only aesthetic function, but also as a shaper of performance narration, through in the form of signs, ornaments, colors and icons. The context of visual communication elements had become part of the message conveyed in the show. Keywords: Kuda Renggong, visual communication, costume, Sumedang ABSTRAK Kuda Renggong adalah kesenian tradisional khas Kabupaten Sumedang, yang mengguna- kan kuda sebagai media ekspresi utamanya. Kekhasan pertunjukan Kuda Renggong adalah pada tata visual, yakni berupa acuk pada kuda. Metode penelitian ini menggunakan pendekatan etnosemiotik, dengan hasil berupa makna-makna interpretatif. Acuk kuda tidak saja berfungsi estetis, tetapi juga menjadi bagian dari narasi pertunjukan, melalui tanda-tanda yang melekat pada bentuk, ornamen, warna dan ikon di dalamnya. Dalam kontek komunikasi elemen visual tersebut menjadi bagian dari pesan yang disampaikan dalam pertunjukan. Kata kunci: Kuda Renggong, komunikasi visual, acuk, Sumedang